Comparative Study of Micronutrients in Soil and Plant Using Microwave Extraction in Wheat Fields of Lahore Suburbs, Pakistan - Mubarak, Shafaq; Zia-ur-Rehman, Muhammad; Haque, Attika (Asian Journal of Chemistry, 2012)
In the present study, microwave digestion methodology is utilized to evaluate the micronutrient contents in soil and wheat leaves samples taken from different fields of Chuck 62 of Lahore city, Pakistan. There is considerable variation among wheat fields in terms of soil characteristics such as pH, EC, moisture, texture and micronutrients. The texture of soil differs from silty clay to silty clay loam. The value of pH, EC and moisture ranged from 5.6-6.9, 0.12-0.21(dS/m) and 0.9-2.3 %, respectively. As far as micronutrient contents are concerned, the values of Zn, Cu, Mn and Fe of bottom soil (15-30 cm) are in range of 71.7-96.4, 8.7-13.3, 208.6-288.7 and 218.2-247.3 mg/kg of soil, respectively. Top soil (0-15 cm) have the values 76.3-88.5, 6.5-15.2, 261.3-296.5, 172.6-241.2 mg/kg. Wheat leaves showed the level of Zn, Cu, Mn and Fe in the range of 40.2-67.3, 4.9-7.4, 112.4-134.7 and 64.2-79.6 mg/kg of soil respectively. The study shows that soil of each field is rich in micronutrients which are available to plants as depicted by the analysis of leaves. There is no need to apply any additional micronutrients to enhance the soil fertility and crop production.